BATASAN PEMIDANAAN PELAKU TINDAK PIDANA KORUPSI DALAM MENGEMBALIKAN KERUGIAN NEGARA - Vayen Lanawaang; Diana Darmayanti Putong; Janeman Jehezkiel Lanawaang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Criminalization is an important element in criminal law, as a guideline and complement to criminal law, where the process of investigation, prosecution, and even verdict in court cannot be separated from criinalization itself. According to practical reason, every crime must be followed by a punishment. According to practical reason, following a crime that was previously committed, imposing the punishment is something that is demanded by ethical justice. According to the modern view, specific prevention as the aim of criminal law the main target to be achieved. Because the purpose of punishment here is directed towards the development or care of the convict, which means that with this punishment he must be developed in such a way that after completing high sentence he becomes a better person than before he received the punishment.